The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1111/1759-7714.12422
|View full text |Cite
|
Sign up to set email alerts
|

Flap endonuclease‐1 rs174538 G>A polymorphisms are associated with the risk of esophageal cancer in a Chinese population

Abstract: BackgroundEsophageal cancer has a high mortality rate, particularly in Asia, and there are obvious racial differences in regard to incidence. The purpose of our study was to assess the genetic susceptibility of functional single nucleotide polymorphisms in flap endonuclease‐1 (FEN1) in esophageal squamous cell carcinoma ESCC.MethodsClinical blood samples of 629 ESCC cases and 686 control samples were collected. The ligation detection reaction method was used to determine FEN 1 rs174538 G>A genotypes.ResultsA s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…They were both upregulated in EC. Despite being implicated in various cancer types, their role in EC has not been studied before [ 64 , 65 , 66 , 67 , 68 ]. Our methodology is validated by some TTAGPs relevant to EC that had previously been confirmed by other authors, for example; FOXA1 was also a highly upregulated DEG, which is known to regulate oestrogen receptor binding in breast cancer [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…They were both upregulated in EC. Despite being implicated in various cancer types, their role in EC has not been studied before [ 64 , 65 , 66 , 67 , 68 ]. Our methodology is validated by some TTAGPs relevant to EC that had previously been confirmed by other authors, for example; FOXA1 was also a highly upregulated DEG, which is known to regulate oestrogen receptor binding in breast cancer [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, due to the complex mechanism of TNBC metastasis, some aspects remain unknown. FEN1 has been identified as a potential biomarker from previous studies, which found that overexpression of FEN1 could disrupt the cell cycle and promote cell proliferation in numerous types of cancer, including breast cancer ( 13 , 24 , 35 , 36 ). Furthermore, FEN1 overexpression was also associated with resistance to chemotherapy ( 18 , 22 ), and targeted therapy ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…Association study with 1840 lung cancer patients and 1958 controls further revealed that these two FEN1 SNPs conferred genetic susceptibility to lung cancer [ 49 ]. Moreover, some evidence was further observed to consolidate the contribution of the rs174538 and rs4246215 to the risk of different types of cancer [ 25 , 36 , 37 , 39 ]. Especially, these two SNPs were shown to decrease breast cancer risk in Chinese [ 25 ]and Iran [ 37 ] populations.…”
Section: Discussionmentioning
confidence: 99%